Pengaruh Brand Image Dan Brand Ambassador Terhadap Keputusan Pembelian Sabun Muka Garnier Pada Mahasiswa di Surabaya - Achmad Dhani Winarno; Zumrotul Fitriyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The reason of this ponder was to discover out how brand picture and brand envoys impact the choice to buy Garnier facial cleanser for understudies in Surabaya. This investigate strategy is quantitative by taking a test of 110 respondents. The populace in this think about were understudies in Surabaya. Whereas the test in this ponder was taken by nonprobability testing strategy with accidental examining strategy. The test comprised of respondents who had acquired Garnier facial cleanser. The information utilized in this consider are essential information and auxiliary information. The investigation procedure utilized in this inquire about is (PLS) with legitimacy test, unwavering quality test and speculation test. The comes about of this think about demonstrate that brand picture incorporates a noteworthy (positive) impact on buy choice. Brand envoy has no noteworthy (positive) impact on acquiring choices. Keywords: Brand Image Brand Ambassador, Purchase Decision